Slower recovery of outpatient clinics than inpatient services for stroke and other neurological diseases after COVID‐19 Pandemic - Zhao, Jing (CNS Neurosci Ther, 2020)
BACKGROUND: In this brief report, we investigated the impact of COVID‐19 on outpatient stroke clinics and inpatient services and their recovery process. METHODS: We sent a survey to physicians worldwide through the network of the World Stroke Organization to investigate the impact of COVID‐19 on stroke clinics. To farther along in recovering from the outbreak, we reviewed stroke and other neurology outpatient clinic visits (approximately 50% were stroke related) and the number of inpatient services from December 2019 to July 2020 in a large neurology department in Shanghai, China, where there was no official city lockdown. RESULTS: We received 112 valid survey responses from 46 countries, representing all continents except for Antarctica. Only seven of the survey responders (7/112, 6.3%) reported that they have kept their outpatient clinics open as usual, but they did exercise increased precautions for COVID‐19 by following recent guidelines regarding use of personal protective equipment and isolation techniques. The remainder of the respondents have either reduced outpatient clinic services or suspended outpatient clinics completely. Telephone consultation or telemedicine with video capability was used for new patients or follow‐ups, with limited in‐person evaluations when necessary. Outpatient clinic visits and inpatient services from a large tertiary hospital in China decreased dramatically during the peak period of the outbreak, but then rebounded back quickly following the partial or full recovery from the outbreak. Compared with the recovery process of inpatient services, outpatient clinic visits decreased faster and recovered much slower. This is consistent with our global survey data which indicates that some outpatient clinics have rescheduled their outpatient visits for 3 to 6 months. CONCLUSIONS: The COVID‐19 pandemic caused a significant drop of in‐person outpatient visits and inpatient services. Clinic visits recovered slower than inpatient services in stroke and other neurological diseases after the pandemic.